Prognostic factors for patients with esophageal cancer who achieve pathological complete response in the primary tumor after upfront chemotherapy or chemoradiotherapy - Masaaki Motoori; Koji Tanaka; Hiroshi Miyata; Makoto Yamasaki; Osamu Shiraishi; Atsushi Takeno; Tomoki Makino; Keijiro Sugimura; Takushi Yasuda; Yuichiro Doki (Annals of Gastroenterological Surgery, 2025)
Abstract Aim Upfront chemotherapy (uCT) or upfront chemoradiotherapy (uCRT) followed by surgery is generally accepted as the standard treatment for patients with locally advanced esophageal cancer. A substantial proportion of patients achieve a pathological complete response (pCR) of the primary tumor with upfront treatment. This retrospective study aimed to clarify the prognostic factors of patients with esophageal cancer who achieve pCR in the primary tumor after upfront treatment and whether the prognosis of patients with pCR who receive uCT differs from that of patients who receive uCRT. Methods This study included 121 patients who achieved pCR of the primary tumor after uCT and 40 patients after uCRT. Univariate and multivariate survival analyses were performed. Results Multivariate analysis of overall survival demonstrated that gender, upfront treatment, and pathological lymph node metastasis were independent prognostic factors (p = 0.0086, 0.011, and 0.031, respectively). Multivariate analysis of relapse‐free survival demonstrated that gender, cM status, and pathological lymph node metastasis were independent prognostic factors (p = 0.033, 0.014, and 0.0010, respectively). Among patients without pathological lymph node metastasis, the uCT group showed significantly better both overall and relapse‐free survival than the uCRT group (p = 0.014 and 0.037, respectively). Recurrence occurred in 24 patients in the uCT group and 9 in the uCRT group. All of local treatment (chemoradiotherapy and surgery) for recurrent lesions was performed in the uCT group. Conclusions Male genders and pathological lymph node metastasis are independent poor prognostic factors in patients with esophageal cancer who receive upfront treatment followed by surgery and achieved pCR of the primary tumor.